Perceptions of the pregnant in the accomplishment of the test Anti-HIV (ELISA) in a center of examination and advice in STD/Aids in a City in the State of Minas Gerais - Souza, Nilzemar R.; Carmo, Tânia Maria D.; Bernardes, Elexandra Helena; Silva, Aline T.; Lima, Ana Paula (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: perinatal or vertical transmission of the HIV can occur intra-uterus, or during labor and after-childbirth through the maternal suckling. Health professionals play an important role and in the clarification of the importance of the accomplishment of the test anti-HIV. Objective: to iden tify the emotions and feelings that the pregnant have when accomplishing the anti-HIV test. Methods: of qualitative appraach, through semi-structu red interview and consults to handbooks, 13 pregnant women who attended consultations, at the nursery, where interviewed where they did the anti- HIV test in ambulatory service in STD/Aids of the College of Nursing of Passos/MG and when they received the results. Results: based on this study it was possible to conclude that there are imperfections in the accompaniment of the pregnant when the indication of the test anti-HIV is con cerned, due to bond lack between pregnant- health professional in the consultations. I and women are not structed on the importance of the accom plishment of the test and how much it can benefit their health and their babies. We also observed that the women are more vulnerable to acquire any transmissible disease, for the fact of trusting their partners; they think that loving be prevented is enough to. Conclusion: once they face the unk nown with the accomplishment of the anti-HIV test, different emotional states were common in the behaviour and espeeches of there pregnant, what suggests that it is a favorable moment for the health professional to accomplish a relationship of help, decreasing the fears and tensions of costumers, thus providing one rapport during the accompaniment.